Patient Concerns and Anxiety Regarding Orthodontic Treatment and appointments during COVID-19 Pandemic - Faiza Malik, Hida Tajasar, Sundas Ali, Kashif Haroon, Hooria Haq, Fiza Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine patient concerns and anxiety regarding orthodontic treatment and appointments during COVID-19 Pandemic Methodology: After approval from Sharif Medical Research Center (SMRC) and the Ethics Committee of Sharif Medical City Hospital (SMCH), 247 orthodontic patients were selected from the Orthodontics Department of SMCH, Lahore, who had on-going orthodontic treatment. The total duration of the study was two and a half months from 12th March to 30th May 2021. Data was analyzed by IBM SPSS version 25. Percentages of the responses in each domain of the questionnaire were calculated. Chi-square test, one-way ANOVA and Pearson’s correlation coefficient were applied where applicable to determine the significance of associations between different variables, with p<0.05 taken as significant. Results: Two hundred and forty seven patients were sent the questionnaire links, while 213 patients responded, out of which 132 were females and 81 were males, with mean age 22.81±2.93 years. Anxiety about the coronavirus pandemic ranged from 5.32 ±2.30. Patients were particularly concerned about the length of time it would take to complete their orthodontic treatment as a result of quarantine (55.9 percent). 5.68±2.15 was the mean anxiety level. Conclusion: The quarantine recommended due to the COVID-19 pandemic impacted orthodontic appointments and patients’ anxieties and anxiety, since a statistically significant correlation was established between quarantine and coronavirus sentiments and orthodontic appointment willingness. Males were more willing to get braces than females. Delay in treatment end, bracket breaking, and growing malocclusion were patients’ top concerns. Patients said the most critical precaution in orthodontics was changing the dentists’ disposable lab coats after every visit to avoid cross-contamination.